Phytochemical analysis, antioxidant potential, and cytotoxic activity of extracts of Quisqualis indica L. - Verma, Ajay; AKS Rawat (Journal of Applied Pharmaceutical Research, 2025)
Background: The present study investigates the antioxidant and cytotoxic potential of the 50% hydroalcoholic extract of Quisqualis indica leaves. Methodology: Phytochemical screening was conducted to determine the presence of phenolics and flavonoids. TPC and TFC were analyzed using the Folin–Ciocalteu method and the aluminum chloride colorimetric assay, respectively. The antioxidant activity was evaluated through the DPPH radical scavenging assay at concentrations ranging from 10 to 100 µg/mL. Cytotoxicity was assessed in A549 human lung carcinoma cells using the MTT assay with extract concentrations from 0 to 1000 µg/mL. Results and Discussion: Phytochemical analysis confirmed the presence of phenolics and flavonoids, with total phenolic content measured as 9.25 ± 0.081 mg gallic acid equivalents (GAE)/g 50% hydroalcoholic extract and total flavonoid content as 4.33 ± 0.24 mg quercetin equivalents (QE)/g 50% hydroalcoholic extract. Antioxidant activity was assessed using the DPPH radical scavenging assay across extract concentrations ranging from 10 to 100 μg/mL. The 50% hydroalcoholic extract exhibited a dose-dependent antioxidant effect with an IC50 value of 48.56 μg/mL. Cytotoxicity was evaluated against A549 human lung carcinoma cells using the MTT assay, with treatments administered at concentrations ranging from 0 to 1000 μg/mL. The extract demonstrated significant cytotoxicity with an IC50 value of 4.76 μg/mL. Conclusion: These findings suggest that Q. indica may serve as a potential source of bioactive compounds with antioxidant and anticancer activities, warranting further investigation through in vivo and mechanistic studies.